Implementation of the internet of things in the global library environment: bibliometric analysis - Borysov, O. (ХДАК, 2023)
The relevance of the topic. Even though the potential of IoT in optimizing library processes and creating innovative services is meaningful, we can observe a lack of research focused precisely on the implementation and application of IoT in libraries. Studying IoT in the context of libraries requires an in-depth analysis and a systematic approach to expand the opportunities for developing recommendations and guidelines for library institutions. The purpose of the article is to analyze bibliometric data obtained from the Scopus scientometric database concerning the application of Internet of Things technologies in library and information production. The methodology of the research includes the methods of analyzing information regarding data obtained from the Scopus database and its generalization. Conclusions. The analysis and systematization of data from the Scopus database showed that research focuses on innovative applications of IoT, data security, and library services’ development. The identifi ed trends and dynamics of publications indicate that the role of IoT technologies in the modern library sector is persistently growing. Given the increasing number of publications from 2010 to 2022, a positive trend in the number of scientifi c studies in this area is expected, especially after the reduction of COVID-19 related quarantine restrictions. These conclusions can serve as a foundation for further research and the development of strategies for implementing IoT in libraries. Scientifi c novelty of the paper is evident because no article containing the analysis of bibliometric data in the sphere of library industry has ever been published. These data were retrieved from the Scopus scientometric database concerning the application of the Internet of Things technologies in libraries worldwide.
Keywords: інтернет речей у бібліотеках; internet of things; цифровізація бібліотек; digitization of libraries